Study on The Development of Guidance System Technology for 122-140 mm Artillery Rocket - Nugroho, Widianto; Riyadl, Ahmad; Muslimin, Ahmad Novi; Setiawan, Rudi; Triharjanto, Robertus Heru; Yogaswara, Y. H. (BRIN Publishing, 2021)
The increase in rocket Artillery accuracy means there will be fewer rockets to be used to destroy a target. This could reduce the needed budget and risk of weapon mobilization. Therefore, this research investigates the advancement in the guidance system technology for Artillery rockets, especially for 122-140 mm caliber. The objective of the research is to find a direction for the development guidance system for the Indonesian Artillery rocket (RHAN). The research use the descriptive-analytic method, in which data was collected from literature studies and inductive analysis was performed. The data shows two kinds of actuators were used, a canard and thrusters. In canard mode, 2 strategies were used, i.e. with bearing to isolate the roll from the rocket, in which 5 control algorithms were used, and without bearing, which 2 control algorithms were used. In thruster mode, there was 5 control algorithms used. Further analysis shows that the best performance is obtained from 2 modes of the canard strategy with bearing, and 2 modes of the thruster strategy. Therefore, it is concluded that the 4 modes can be used to be implemented in RHAN which needs to be added to the control system.